Development of a spirulina feed effective only for the two larval stages of Schistosoma mansoni, not the intermediate host mollusc - Takashi Kumagai; Masaaki Miyamoto; Yurino Koseki; Yasuyuki Imai; Tomoko Ishino (Tropical Medicine and Health)
Abstract Background Schistosomiasis control relies primarily on mass drug administration with praziquantel. However, persistent reinfection and high treatment costs remain significant challenges. Current strategies largely overlook intermediate host molluscs and infected larvae, which are critical sources of transmission. Niclosamide, the only widely used molluscicide, is limited by its high environmental toxicity and cost, creating a need for safer and more sustainable alternatives. Methods In this study, we investigated the effects of a spirulina-based feed derived from the cyanobacterium Arthrospira platensis on infected snails. Laboratory experiments were conducted to assess the impact of spirulina on cercariae release from infected snails. We further examined the safety profile of spirulina by testing its effects on both snails and Japanese medaka. Additionally, the direct effects of spirulina constituents on cercariae viability were evaluated. Results Snails fed spirulina presented a significant reduction in cercariae output, with reductions of up to 88%. The reduction was concentration dependent and more pronounced during the early stages of infection. Spirulina had no toxic effects on either snails or Japanese medakas. Further analysis revealed that the active ingredient causing the increase in mortality in cercaria was linoleic acid, a common ingredient in both the spirulina feed and the base feed, and a direct anti-parasitic effect of linoleic acid was confirmed. Conclusion Spirulina represents a promising, environmentally safe feed that can reduce the transmission of schistosomiasis by directly impacting schistosome larvae within infected snails and reducing the release of cercariae. This novel approach offers a sustainable and nontoxic alternative to current molluscicidal strategies and may contribute to more effective and environmentally friendly schistosomiasis control.